2018
DOI: 10.1177/1024907918802069
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for special care units admission and in-hospital mortality among geriatric patients that presented to the emergency department of a teaching hospital

Abstract: Background: The world population is experiencing ageing and this phenomenon certainly gives significant impact to the social, economic as well as health care services globally. Objectives: This study aimed to determine the prevalence of geriatric patients treated in critical zone in an emergency department of a teaching hospital and the factors associated with special care units admission and in-hospital mortality. Methods: A single-centre prospective cross-sectional study was carried out from 1 January 2016 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The requirement of vasopressors in elderly ICU patients is significantly associated with poor outcomes in this study, which is in agreement with earlier reports. 2 , 6 , 24 , 26 28 The mortality rate for intubated patients was 28.7%, whereas previous published reports reported mortality rates ranging from 20.3 to 51%. 25 Previous research has shown that the intubation and receipt of mechanical ventilation were associated with increased mortality in elderly ICU patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The requirement of vasopressors in elderly ICU patients is significantly associated with poor outcomes in this study, which is in agreement with earlier reports. 2 , 6 , 24 , 26 28 The mortality rate for intubated patients was 28.7%, whereas previous published reports reported mortality rates ranging from 20.3 to 51%. 25 Previous research has shown that the intubation and receipt of mechanical ventilation were associated with increased mortality in elderly ICU patients.…”
Section: Discussionmentioning
confidence: 95%
“… 25 Previous research has shown that the intubation and receipt of mechanical ventilation were associated with increased mortality in elderly ICU patients. 2 , 5 , 13 , 26 28 …”
Section: Discussionmentioning
confidence: 99%